Discoid resection for colorectal endometriosis: results from a prospective cohort from two French tertiary referral centres. (3rd July 2019) - Abo, C.; Bendifallah, S.; Jayot, A.; Nyangoh Timoh, K.; Tuech, J.‐J.; Roman, H.; Daraï, E.
Abstract: Aim: Using a prospective database of discoid resection performed in two tertiary referral centres, the aim of this study is to assess the feasibility, short‐term complication rates and clinical outcomes, including voiding dysfunction, of the procedure. Method: A retrospective analysis of a prospective cohort database was conducted from February 2010 to October 2017 in two tertiary referral centres. One hundred and forty‐eight consecutive patients scheduled for colorectal endometriosis by discoid resection were enrolled. The median follow‐up was 21 months. All the women underwent complete preoperative assessment (MRI, transvaginal ultrasonography and rectal echo‐endoscopy) before the removal of colorectal endometriosis. Postoperative complications were classified according to the Clavien–Dindo classification system as minor (grades I and II) or major (grades IIIA, IIIB and IV). Cases of voiding dysfunction were also noted. Results: The procedure was abandoned in seven patients. In 91 (64.5%) of the remaining 141 patients, the diameter of discoid resection removed was ≥ 30 mm. Surgery was performed by laparoscopy in 137/141 cases (92.7%). Grade I–III complications were observed in 37 patients (26.2%) with 11 grade IIIb (7.8%). Postoperative voiding dysfunction occurred in 16 patients (11.3%), 11 of whom required self‐catheterization for < 1 month. In a multivariate analysis including age, body mass index, lesion size and history of previous surgery for endometriosis, a history of previous surgery was independently correlated to complication outcome ( P  = 0.043). Conclusions: This analysis suggests that discoid resection is associated with good short‐term results for women with colorectal endometriosis in a tertiary referral centre as it is associated with a low rate of postoperative complications.